Nghiên cứu khả năng chống ăn mòn mài mòn của lớp phủ hợp kim NiCr20 được thẩm thấu với photphat nhôm trong môi trường axit - Tuấn, Nguyễn Văn; Hà, Phạm Thị; Lý, Phạm Thị; Quân, Võ An; Mai Thanh, Đinh Thị; Quý, Lê Thu; Roãn, Phạm Đức (Vietnam Journal of Chemistry, 2017)
The corrosive wear resistance of NiCr20 alloy coating (NC) impregnated by aluminum phosphate and heat-treated at 600 oC (NA6) and 1000 oC (NA10) was investigated in acid H2SO4 pH = 2 containing SiO2 3 % by weight; the flow velocity is 4 m/s. The analysis of X-ray diffraction (XRD) showed that, the stable crystalline phases in acidic media such as AlPO4 and Al(PO3)3 which were formed on NA6 coating’s surface made corrosive wear resistance of NA6 coating increase in comparison with the resistance measured on NA10 and NC coating samples. The formation of unstable crystalline phases such as Al36P36O144 and Ni3(PO4)2 in NA10 coating caused the corrosive wear resistance of NA10 coating smaller than that one measured on NC coating. After 168 hours of corrosive wear test, the thickness of NA6 coating reduced to about 47 μm, while it was about 67 μm for NC coating. Keywords. Thermal spray, aluminum phosphate sealant, acidic corrosion, corrosion wear.